ADOPSI INOVASI PETANI KELAPA SAWIT TERHADAP SISTEM INTEGRASI SAPI – KELAPA SAWIT (SISKA) DI KABUPATEN PELALAWAN - Situmorang, Bungaran; Edwina, Susy; Maharani, Evi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study proposed to analyze  process of innovation-adopted by the palm farmer and to analyze the level of innovation-adopted by the palm farmer to   Palm – Cow Integrated System (SISKA) in Pelalawan Regency. This research took place in Mulya Subur Village, Kerumutan Village, and Meranti Village in Pelalawan Regency. This place is taken by purposive, considered by some areas applied SISKA in Pelalawan Regency. The respondens are taken by sensus method and total samples are 33 farmers. The data analyzed by descriptive methode. The purpose were analyzed by Likert-Scale. The level of innovation-adopted refers to Rogers Theory that saw the average sum of each score stages innovation adoption. The result showed  that  process of innovation-adopted by the palm farmer to SISKA in Pelalawan Regency consist of five number stages are knowledge, persuation, decision making, implementation, and confirmation. The stage of knowledge was categorized as high. The stage of persuation was categorized as high. The stages of decision making consist of two parts namely, decision to adopted SISKA was categorized as high and decision not to adopted SISKA was categorized as low. The stage of implementation was categorized as medium. The last stage is confirmation and it was categorized as medium. The level of innovation-adopted by the palm farmers to SISKA is totality grouped as medium category.   Keywords: Adoption, Innovation, Palm – Cow Integrated System (SISKA)